Nonergodic Quadratic Operators for a Two-Sex Population - Ganikhodzhaev, N. N.; Zhamilov, U. U.; Mukhitdinov, R. T. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We describe the structure of quadratic operators of a two-sex population that differs from the model studied by Lyubich and give an example of nonergodic quadratic operator for a two-sex population.